Difference analysis of Xiaoqu light-flavor Baijiu brewed with different varieties of rice - MA Zhenbing, GONG Lijuan (Zhongguo niangzao)
In order to explore the differences of Xiaoqu light-flavor (Qingxiangxing) Baijiu brewed with different varieties of rice, the physicochemical indexes, cooking characteristics, brewing characteristics and flavor components of Xiaoqu light-flavor Baijiu brewed with different rice varieties (Gangyou 188, Teyou 94, Gangyou 900 and Chuanliangyou No.1) were analyzed by differential scanning calorimeter (DSC), rapid viscosity analyzer (RVA), conventional detection methods and GC-MS, and the correlation of the results was analyzed. The results showed that Chuanliangyou No.1 had the highest crude protein content, amylopectin content, and amylopectin to amylose ratio (8.99, 61.04%, 3.82), Teyou 94 had the highest crude fat content (2.1%), Gangyou 188 had the highest crude starch, starch utilization rate and liquor yield (79.71%, 93.6%, 44.6%). The contents of ethyl acetate and ethyl lactate were the highest in Gangyou 188, which were 112.79 mg/L and 30.13 mg/L, respectively. Chuanliangyou No. 1 had the lowest enthalpy (11.92 J/g). The gelatinization temperature of Teyou 94 was the lowest (80.83 ℃). Gangyou 900 had the lowest regenerative value (1 723 cp). The correlation results showed that there were significant positive correlations between termination temperature and moisture, pasting temperature and crude starch content, final viscosity and valley viscosity, recovery value and final viscosity (P<0.05), the starch utilization rates and liquor yield were significantly negatively correlated with crude fat (P<0.05), and liquor yield was significantly positively correlated with crude starch and amylopectin content (P<0.05). To sum up, Gangyou 188 was a relatively ideal raw material for brewing Xiaoqu light-flavor Baijiu.